Composition, Repellent, and Insecticidal Activities of Two South American Plants against the Stored Grain Pests Tribolium castaneum and Tribolium confusum (Coleoptera: Tenebrionidae). (20th February 2014) - Benzi, Verónica; Stefanazzi, Natalia; Murray, Ana Paula; Werdin González, Jorge O.; Ferrero, Adriana
Abstract : As part of a screening program to evaluate the biological activity of indigenous plants, we report the composition and the bioactivity of essential oils (EOs) extracted from Té de Burro Aloysia polystachya [(Griseb.) Moldenke] and Lemon Verbena Aloysia citriodora [Palau] against two of the most widespread secondary pests of stored products, the red flour beetle Tribolium castaneum [Herbst] and the confused flour beetle Tribolium confusum [Jacqueline du Val]. Analysis by gas chromatography-mass spectrometry of the EOs led the identification of their major constituents and their relative proportions. EO of A. citriodora showed the highest repellent activity against both beetles (>70%). On the other hand, both plants showed fumigant toxicity only against T. confusum, without significant differences between them (LC50 values of 5.92 and 5.53 mg/L air for A. polystachya and A. citriodora, resp.). For contact toxicity (topical applications) the EO of A. polystachya was more effective (LD50 = 7.35  μ g/insect) than the EO of A. citriodora (LD50 = 13.8  μ g/insect) only against T. castaneum . On the other hand, T. confusum was not susceptible by contact to any of these EOs. These results provide important tools for the development of an Integrated Pest Management (IPM) program.